2021
DOI: 10.1155/2021/8838420
|View full text |Cite
|
Sign up to set email alerts
|

Improved Corn Yields When Humic Acid Extracted from Composted Manure Is Applied to Acid Soils with Phosphorus Fertilizer

Abstract: Most corn planted on tropical acidic soils suffers substantial yield loss caused by low crop phosphorus (P) uptake. Humic acid is recommended to increase crop P uptake since it is capable of competing with P to be bound to soil adsorption complexes. Humic acid extracted from composted manure (MHA) is a good alternative to humic acid because it is more reactive and has a higher complexation ability compared with leonardite. Therefore, the effectiveness of soil-applied MHA combined with P was evaluated to improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Humic substances are recommended for increasing crop P uptake since they are capable of competing with P to be bound to soil adsorption complexes [44]. In agreement with this, Kaya et al [45] observed that leonardite enhanced leaf P and yield in maize under P and water stress in calcareous soils.…”
Section: Discussionmentioning
confidence: 84%
“…Humic substances are recommended for increasing crop P uptake since they are capable of competing with P to be bound to soil adsorption complexes [44]. In agreement with this, Kaya et al [45] observed that leonardite enhanced leaf P and yield in maize under P and water stress in calcareous soils.…”
Section: Discussionmentioning
confidence: 84%
“…P application increased root length and root volume, which corroborates the finding in wheat, where increased availability of P due to application of biochar increased root length by 1.4–1.8 times (Song et al, 2020 ). Likewise, the application of humic acid (75 mg kg −1 ) and P fertilizer (120 mg P 2 O 5 kg −1 air-dried soil) in corn recorded higher root volume and other root attributes compared with the control (Purwanto et al, 2021 ).…”
Section: Discussionmentioning
confidence: 96%
“…HA has been described to contain organically active functional groups such as the amino, carboxyl, phenolic, hydroxyl, ketone and quinine groups, which play different roles in the soil-plant interface, including the chelation of macro and micronutrients for enhanced uptake by plants that subsequently leads to increased crop yield [29][30][31]. The use of HA in crop production causes increased phosphate uptake, photosynthesis, elongation of root cells, oxygen uptake and the activity of beneficial soil microbes [29,32]. N fertilization of squash and other related crops has been shown to consistently improve crop yields [8,33].…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of nitrate accumulation in plants due to the application of HA has been associated with the ability of HA to activate some key metabolic events in plants, such as the increased production of reductase enzymes [43,44]. In addition, the use of HA with chemical fertilizer application has been reported to have the potential to significantly improve soil fertility and crop yield [31,32]. Nitrate is made directly available for plant uptake on the application of N fertilizers, while it is only made available after the decomposition of organic materials such as composts, manures and crop straw [42].…”
Section: Discussionmentioning
confidence: 99%